2014
DOI: 10.4236/jwarp.2014.65049
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Geopolymers Using Local Resources for Construction and Water Purification

Abstract: Large deposits of impure kaolins exist in Jordan and many parts of the world; geoplymers can reduce environmental impacts and have multi-application in many fields, such as water purification, waste treatment, fire proof construction, etc. The aim of this research is to investigate the use of alkali activated zeolitic tuff and low purity metakaolin as precursors for the production of functional geoplymers exhibiting proper mechanical properties and high potential for water storage and decontamination of pollut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…It has been suggested that the adsorption properties of AAMs could be utilized in construction materials such as water tanks, pipes, and damns (Alshaaer et al 2012;Yousef et al 2009;Alshaaer et al 2010;Hamaideh et al 2014). Good mechanical properties combined with adsorption capacity could be obtained if zeolitic tuff is used as fine aggregate in AAM binder (Andrejkovicová et al 2016;Huang et al 2012).…”
Section: Preparationmentioning
confidence: 99%
“…It has been suggested that the adsorption properties of AAMs could be utilized in construction materials such as water tanks, pipes, and damns (Alshaaer et al 2012;Yousef et al 2009;Alshaaer et al 2010;Hamaideh et al 2014). Good mechanical properties combined with adsorption capacity could be obtained if zeolitic tuff is used as fine aggregate in AAM binder (Andrejkovicová et al 2016;Huang et al 2012).…”
Section: Preparationmentioning
confidence: 99%
“…It is worthwhile to point out that the new hybrid material we propose combines good mechanical properties with the capacity to absorb pollutants, as advocated by several authors in the literature, who have recently advanced for other materials based on geopolymers, the possibility to use them also as non-structural construction materials for water tanks, pipes, and damns [54,55].…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…However, also materials obtained from a reaction between alumino-silicate precursors and phosphoric acid are sometimes referred to as acid-activated geopolymers [3]. Geopolymers have recently gained interest in several water and wastewater treatment applications such as adsorbents [4][5][6][7][8][9][10][11], membrane material [12], photocatalysts [13,14], functional construction materials [15,16], or substrate for biofilm reactors [17]. In many of the aforementioned applications, the use of geopolymers is based on their ion exchange capacity and porous structure.…”
Section: Introductionmentioning
confidence: 99%